The Paradigm of Islamic Legal Sociology Towards Counterfeit Books Transactions in The Yogyakarta - Maulana, Diky Faqih; Rozak, Abdul; Mursyid, Achmad Yafik (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2022)
AbstractThe more rapid development of civilization is directly proportional to the rapid pace of economic activity, including the buying and selling activity of counterfeit goods.  In An-Nisa verse 29, it is explained that it is prohibited to eat property in vanity, so according to the Copyright Law the transaction is clearly against the law.  Departing from this background, what is the mechanism for the practice of buying and selling Counterfeit goods?  Why is this practice still being done?  What is the perspective of the sociology of Islamic law on this case?  This type of research is field research, deductive analytic with a sociology of law approach.  The conclusion of this study is, this practice is carried out when a book supplier offers pirated books to sellers at an agreed price or booksellers order from suppliers according to consumer demand.  This practice still occurs due to the demands of the seller's economy, buyers' high interest in reading and weak sanctions.  This practice is included in the category of complaint offense, where if no party feels aggrieved and reports there will be no legal process.  This state in Islam is called 'urf fasid.AbstrakSemakin pesatnya perkembangan peradaban, berbanding lurus dengan pesatnya aktivitas ekonomi tidak terkecuali aktivitas jual beli barang counterfeit. Dalam An-Nisa ayat 29 dijelaskan dilarang memakan harta secara batil, begitupula menurut UU Hak Cipta transaksi tersebut jelas melanggar hukum. Berangkat dari latar belakang tersebut, Bagaimana mekanisme praktik jual beli barang Counterfeit ? Mengapa praktik ini masih dilakukan ? Bagaimana perspektif sosiologi hukum Islam terhadap kasus tersebut ? Jenis penelitian ini adalah field research, bersifat deduktif analitik dengan pendekatan sosiologi hukum. Kesimpulan dari penelitian ini adalah, praktik ini dilakukan ketika supplier buku menawarkan buku bajakan kepada para penjual dengan harga yang disepakati atau penjual buku memesan kepada supplier sesuai permintaan konsumen. Praktik ini masih terjadi karena tuntutan ekonomi penjual, minat baca yang tinggi pembeli dan lemahnya sanksi. Praktik tersebut termasuk kategori delik aduan, dimana apabila tidak ada pihak yang merasa dirugikan dan melaporkan maka tidak akan ada proses hukum. Keadaan ini dalam Islam disebut ‘urf fasid.